1991
DOI: 10.1111/j.1399-6576.1991.tb03302.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and arterial oxygen saturation during preoperative emptying of the stomach

Abstract: We studied the hemodynamic response to preoperative emptying of the stomach by means of a gastric tube in 20 non-fasting non-premedicated patients aged 39 (24-54) (median and quartiles) presenting for emergency surgery. Systolic and diastolic blood pressure and heart rate increased by 24.4% (P less than 0.01), 29.9% (P less than 0.01) and 36% (P less than 0.01), respectively. Arterial oxygen saturation decreased by 2.1% (P less than 0.01). The rate pressure product increased by 68% (P less than 0.01), exceedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Stomach drainage with a gastric tube 17 does not guarantee complete emptying. Also, preoperative insertion of a gastric tube in a nonsedated patient is not without hazards 18 and is only recommended in patients with bowel obstruction. An alternative would be to administer a prokinetic drug before induction of anesthesia.…”
mentioning
confidence: 99%
“…Stomach drainage with a gastric tube 17 does not guarantee complete emptying. Also, preoperative insertion of a gastric tube in a nonsedated patient is not without hazards 18 and is only recommended in patients with bowel obstruction. An alternative would be to administer a prokinetic drug before induction of anesthesia.…”
mentioning
confidence: 99%
“…Vale lembrar que a sondagem gástrica não é um procedimento isento de riscos. Kristensen e col. 42 estudaram a resposta hemodinâmica de 20 indivíduos, não-anestesiados e considerados de estômago cheio que foram submetidos à drenagem pré-operatória do conteúdo gástrico. Segundo os autores, as alterações cardiovasculares foram semelhantes às observadas durante a intubação traqueal de pacientes acordados.…”
Section: Manobra De Sellick E a Sonda Gástricaunclassified
“…One should not forget that the nasogastric tube is not devoid of risks. Kristensen et al 42 evaluated the hemodynamic response of 20 non-anesthetized individuals, considered to be on a full stomach, undergoing preoperative drainage of gastric contents. According to the authors, cardiovascular changes were similar to those observed during tracheal intubation in awake patients.…”
Section: Sellick Maneuver and Nasogastric Tubementioning
confidence: 99%
“…Although stomach tubes do reduce gastric volume, they cannot guarantee an empty stomach. The procedure is extremely inconvenient and may produce detrimental effects both in the baby and mother (12,13). Hence, most authors do not recommend routinely preoperative mechanical e m p tying of the stomach.…”
Section: Rrdricing Gastric Acidity and Volumementioning
confidence: 99%